The Effects of The Ability of Food Processing and Self-efficacy Towards The Interests of The Entrepreneurship - Maemunah, Iin; Iriani, Tuti; Febriana, Rina (INVOTEC, 2019)
The purpose of the study was to determine the effect of the ability to process food and self-efficacy towards the interests of entrepreneurship. The research used a quantitative method with 204 Vocational High School students in culinary study programs taken from three State Vocational Schools in the city of Bekasi, Indonesia. The data were collected using such instruments as interview, documents and questionnaire. The results of the study showed that there was no significant influence the ability to process food towards the interest in entrepreneurship as there was also no significant influence of self-efficacy towards the interest in entrepreneurship. It was also found that state vocational high school students in Bekasi, Indonesia, had very low self-confidence and self-efficacy indicating that they had low motivation for entrepreneurship.